Analisis Kinerja Rantai Pasok Sayuran Hidroponik di Casa Farm Hidroponik - Khansanadhira Rhaina Gelar Gupta Samudera; Eddy Renaldi (Universitas Galuh, 2026)
Casa Farm Hydroponic operates as an agribusiness entity that manages hydroponic vegetable production and collaborates with supplier partners to meet market demand. However, in practice, there are still constraints related to the mismatch between production capacity and demand, which affects order fulfillment and supply chain management performance. This study aims to analyze the supply chain structure, measure the performance of hydroponic vegetable supply chain management, and formulate strategies to improve supply chain management performance at Casa Farm Hydroponic. The study employed a descriptive qualitative approach with a case study design. Data were collected through interviews with Casa Farm management and supplier partners, field observations, and documentation. Supply chain management performance was measured using the Supply Chain Operations Reference (SCOR) model version 12.0, while priority improvement strategies were determined using the Analytical Hierarchy Process (AHP). The results indicate that the overall supply chain management performance of Casa Farm Hydroponic is categorized as good. Nevertheless, performance gaps were identified in the attributes of reliability (Perfect Order Fulfillment), agility (Upside Supply Chain Adaptability), and cost (Cost of Goods Sold). Based on the AHP results, the priority attribute for improvement is asset management efficiency, measured by Cash to Cash Cycle Time. The recommended improvement strategies include strategic sourcing, optimization of technology-based production scheduling, and capacity utilization management to enhance sustainable supply chain management performance.